Information perseveration in recognition memory: Examining the scope of sequential dependencies. - Dollois, Michelle A.; Fenske, Mark J.; Fiacconi, Chris M. (Memory & Cognition, 2025)
Models of recognition memory often assume that decisions are made independently from each other. Yet there is growing evidence that consecutive recognition responses show sequential dependencies, whereby making one response increases the probability of repeating that response from one trial to the next trial. Across six experiments, we replicated this response-related carryover effect using word and nonword stimuli and further demonstrated that the content of the previous trial—both perceptual and conceptual—can also bias the response to the current test probe, with both perceptual (orthographic) and conceptual (semantic) similarity boosting the probability of consecutive "old" responses. Finally, a manipulation of attentional engagement in Experiments 3a and 3b provided little evidence these carryover effects on recognition decisions are merely a product of lapses in attention. Taken together, the current study reinforces prior findings that recognition decisions are not made independently, and that multiple forms of information perseverate across consecutive trials.